Munawir dan Isu Mawarith: Sebuah Kajian Linguistik Pada Al-Nisā Ayat 11 - Saidi, Ali Akbar Bin Sutan; Hussin, Haziyah; Fakhrurrazi, Ahmad; Ahmad, Mohd. Nazri (STIQ Amuntai, 2024)
The law of inheritance is a study that has been stipulated in the Qur'an in detail. This study examines how Munawir Syadali thinks about the division of inheritance and the factors behind the emergence of this thought. This study uses a qualitative approach with a literature study type. The data collection method is document analysis and uses content analysis techniques. The results of this study indicate that H. Munawir Sjadzali's thoughts on verse 11 of Surah An-Nisa' are related to the law of inheritance division, namely to equalize the division of inheritance between sons and daughters. Analysis of Munawir's biography, thoughts, and interpretation methods shows his hermeneutic approach, emphasizing the spirit of justice behind the text of the Qur'an compared to mere literal interpretation. This approach, which takes into account the current social and cultural context, differs from traditional interpretations that adhere to the 2:1 ratio stated in the verse. Several factors have shaped Munawir's views, including his educational background, partnership experience, and commitment to Islamic reform. He prioritizes freedom of thought and contextualization of Islamic teachings, so that they are relevant in the modern world. Although his approach is provocative, he conveys to broader and deeper discussions about the interpretation of the Qur'an and the law of mawarith.